Предмет: Алгебра,
автор: kutuzo98Rocky4
9/x-3 - 3x/(x-3)^2 : 3x/x^2-9 - 2x-3/x-3
упростите при х=2-корень7
Ответы
Автор ответа:
0
3x/(x-3)² : 3x/x²-9 =3x*(x-3)(x+3)/(x-3)² *3x=(x+3)/(x-3)
9/(x-3) - (x+3)/(x-3) -(2x-3)/(x-3)=(9-x-3-2x+3)/(x-3)=(9-3x)/(x-3)=-3(x-3)/(x-3)==-3
9/(x-3) - (x+3)/(x-3) -(2x-3)/(x-3)=(9-x-3-2x+3)/(x-3)=(9-3x)/(x-3)=-3(x-3)/(x-3)==-3
Автор ответа:
0
Спасибо!
Похожие вопросы
Предмет: История,
автор: maratmirzoev15
Предмет: Математика,
автор: plehanovmihail99
Предмет: Алгебра,
автор: Edikud
Предмет: Информатика,
автор: beasik
Предмет: География,
автор: gavrilova70